2014
DOI: 10.1136/bmj.g3725
|View full text |Cite
|
Sign up to set email alerts
|

Evidence based medicine: a movement in crisis?

Abstract: Trisha Greenhalgh and colleagues argue that, although evidence based medicine has had many benefits, it has also had some negative unintended consequences. They offer a preliminary agenda for the movement’s renaissance, refocusing on providing useable evidence that can be combined with context and professional expertise so that individual patients get optimal treatment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
1,230
0
46

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,400 publications
(1,334 citation statements)
references
References 60 publications
9
1,230
0
46
Order By: Relevance
“…It also means that it is difficult to control each arm of an RCT study design. It has therefore been suggested [78] that the integration of realist evaluation within an RCT design may be more appropriate for evidence-based medicine whereby "statistically significant benefits may be marginal in clinical practice" [79].…”
Section: Discussionmentioning
confidence: 99%
“…It also means that it is difficult to control each arm of an RCT study design. It has therefore been suggested [78] that the integration of realist evaluation within an RCT design may be more appropriate for evidence-based medicine whereby "statistically significant benefits may be marginal in clinical practice" [79].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of systematic reviews generated by a national knowledge centre to inform policymaking in Norway showed that in most cases, the evidence base addressed only a fraction of relevant policy questions 40. More generally, there is growing evidence that the science of systematic reviews is becoming increasingly distorted by commercial and other conflicts of interest, leading to reviews, which—often despite ticking the boxes on various quality checklists—are unnecessary, misleading or partisan 19, 41. The holy grail of a comprehensive database of unambiguous and unbiased evidence summaries (in pursuit of which the Cochrane Collaboration was founded42) continues to recede into the future.…”
Section: Systematic or Narrative Or Systematic And Narrative?mentioning
confidence: 99%
“…In addition, there are difficulties in accommodating person-centred health care principles of shared decision making, patient values, preferences, choice and control to the recommendations Rosner, 2012;Salvador-Carulla et al 2013;Greenhalgh et al 2014Greenhalgh et al , 2015Fernandez et al 2015;Bingeman, 2016). A series of biases related to this challenge have been enumerated Rosner, 2012;SalvadorCarulla et al 2013;Greenhalgh et al 2014Greenhalgh et al , 2015Fernandez et al 2015;Bingeman, 2016). Increasing emphasis has been placed on the involvement of consumers in the development of guidelines (Schunemann et al 2006;Nilsen et al 2010;Guideline International Network (GIN), 2015).…”
Section: What Are the Mainstream Solutions To Improve Guideline Develmentioning
confidence: 99%